Clinical and hemostatic characteristics of women with menopausal syndrome receiving the «Extra youth» dietary supplement - J. Kh. Khizroeva; V. O. Bitsadze; N. A. Makatsariya; E. S. Egorova; N. N. Babaeva (IRBIS LLC, 2019)
Aim: to study the clinical and hemostatic changes in women with menopausal syndrome (MS), receiving the dietary supplement Doctor sea «Extra youth» (EY), containing hydrolyzed caviar of sea urchins, calcium alginate and rosehip extract. Materials and methods. The study involved 60 women with MS aged 45-55 years. The patients were divided into 2 groups: the main group consisted of 30 women who received the EY supplement, the comparison group - 30 women who received no EY. During the study, women in the main group received two EY capsules twice a day for 1 month. The severity of the menopausal symptoms and the characteristics of hemostasis before and after taking the EY were evaluated. Results. After 1 month on the EY, the menopausal symptoms (hot flashes, sweating, heart palpitations, nervousness, fatigue) alleviated, general well-being improved, and a better hemostatic performance occurred (chronometric and structural hypercoagulation, a decrease in platelet aggregation and the D-dimer level). Conclusion. The dietary supplement EY can be recommended for use in general clinical practice as a means to improve the well-being of women in pre- and post-menopausal period and also to prevent thrombotic complications.